Beispiel Nr: 05
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 1 x +3 y =9\\ 3 x -2 y = -6 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 1 x +3 y =9\\ II \qquad 3 x -2 y = -6 \\ \text{I nach y auflösen}\\ 1 x +3 y =9 \\ 1 x +3 y =9 \qquad /-1 x\\ 3 y =9 -1 x \qquad /:3 \\ y =3 -\frac{1}{3} x \\ \text{II nach y auflösen}\\ 3 x -2 y =-6 \\ 3 x -2 y =-6 \qquad /-3 x\\ -2 y =-6 -3 x \qquad /:\left(-2\right) \\ y =3 +1\frac{1}{2} x \\ \text{I = II}\\ 3 -\frac{1}{3} x =3 +1\frac{1}{2} x \qquad /+\frac{1}{3} x /-3 \\ 3-3 =1\frac{1}{2} x +\frac{1}{3} x \\ 0 =1\frac{5}{6} x \qquad /:1\frac{5}{6} \\ x=0 \\ \text{x in I}\\ y =3 -\frac{1}{3} \cdot 0 \\ y=3 \\ L=\{0/3\} \end{array} & \begin{array}{l} I \qquad 1 x +3 y =9\\ II \qquad 3 x -2 y = -6 \\ \text{I nach x auflösen}\\ 1 x +3 y =9 \\ 1 x +3 y =9 \qquad /-3 y\\ 1 x =9 -3 y \qquad /:1 \\ x =9 -3 y \\ \text{II nach x auflösen}\\ 3 x -2 y =-6 \\ 3 x -2 y =-6 \qquad /+2 y\\ 3 x =-6 +2 y \qquad /:3 \\ x =-2 +\frac{2}{3} y \\ \text{I = II}\\ 9 -3 y =-2 +\frac{2}{3} y \qquad /+3 y /+2 \\ 9+2 =\frac{2}{3} y +3 y \\ 11 =3\frac{2}{3} y \qquad /:3\frac{2}{3} \\ y=3 \\ \text{y in I}\\ x =9 -3 \cdot 3 \\ x=0 \\ L=\{0/3\} \end{array} \end{array} $